The Evolution in The Field of Anticorruption in The Health Sector in Italy - Alessandro Mauro Tavone; Andrea Cammarano; Giulia Ceccobelli; Gabriele Giuga; Gian Luca Marella (Jurnal Kesehatan Masyarakat, 2025)
The fight against corruption within the healthcare sector in Italy has undergone significant transformation following the introduction of Law n. 190/2012. This legislation marked a pivotal step towards establishing a comprehensive system aimed at preventing corruption through a blend of preventive measures, transparency, and administrative reorganization. Central to these efforts is the Italian National Anti-Corruption Authority (ANAC) and the National Anti-Corruption Plan (PNA), which provide structured guidelines and strategies for public administrations, including healthcare entities. This study examines the evolution and impact of anti-corruption measures in the Italian healthcare sector, focusing on key legislative and regulatory frameworks, particularly the roles played by ANAC and the PNA. The commentary explores the implementation of these measures, highlighting the innovative approaches and the challenges encountered. Significant milestones include the legislative updates, such as the Legislative Decree n. 231/2001, which introduced administrative liability for corporate crimes, and the more recent resolution n. 605/2023, which reinforces digital procurement processes, real-time data analytics, and enhanced transparency in healthcare administration. These updates align with broader national recovery efforts post-COVID-19 and aim to foster a culture of integrity and accountability within the sector. Key findings reveal that while there has been considerable progress in enhancing transparency and reducing corruption risks, challenges remain. These include resource constraints, complexity of integrating new measures with existing systems, stakeholder engagement, and ensuring rigorous monitoring and enforcement. Addressing these challenges is critical for sustaining the progress achieved and further improving the effectiveness of anti-corruption strategies. The continuous refinement of the PNA and its application within the healthcare sector illustrates a robust commitment by Italian authorities to uphold public trust and prevent corruption.